1970
DOI: 10.5254/1.3547316
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate Reactions with Difunctional Polyisobutylenes

Abstract: The reactions of isocyanates with carboxy terminated polyisobutylenes, CTPIB, and with hydroxy terminated polyisobutylenes, HTPIB, have been studied in detail. In the case of HTPIB specific emphasis has been given to an hydroxy-ester functionality prepared by the base catalyzed reaction of CTPIB with propylene oxide. Isocyanate reactions with polymeric carboxyl groups were studied to observe if conditions could be established to remove quickly the undesirable carbon dioxide by-product. A potential advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Among early developments, the contribution by Zapp et al must also be mentioned 12. These authors prepared polyisobutylene‐based polyurethanes by the use of sec‐ OH‐telechelic polyisobutylenes, HOCH(CH 3 )CH 2 ‐PIB‐CH 2 CH(CH 3 )OH, in combination with a conventional diisocyanate (toluyl diisocyanate).…”
Section: Early Developments: the First Well‐defined Ho‐pib‐ohs And Pimentioning
confidence: 99%
“…Among early developments, the contribution by Zapp et al must also be mentioned 12. These authors prepared polyisobutylene‐based polyurethanes by the use of sec‐ OH‐telechelic polyisobutylenes, HOCH(CH 3 )CH 2 ‐PIB‐CH 2 CH(CH 3 )OH, in combination with a conventional diisocyanate (toluyl diisocyanate).…”
Section: Early Developments: the First Well‐defined Ho‐pib‐ohs And Pimentioning
confidence: 99%
“…1 PIB-based thermoplastic polyurethane (PU) elastomers represent a particularly interesting class of biomaterials and have attracted much attention. 5 Kennedy et al reported the synthesis of PIB-based PUs by the use of well-defined hydroxy-telechelic PIB (HO-PIB-OH), diisocyanates and chain extenders; 6 those materials exhibited excellent chemical and thermal stability. 4 As early as in 1970, Zapp et al prepared PIB-based PUs utilizing sec-hydroxy-telechelic PIB.…”
mentioning
confidence: 99%
“…The anhydrides subsequently evolve carbon dioxide to yield amines at elevated temperatures (70)(71)(72). The aromatic amines are further converted into amides by reaction with excess anhydride.…”
Section: Addition Polymersmentioning
confidence: 99%